The main disadvantages in the teaching of graphic disciplines and how to eliminate them - Tuleuov, Gulmarzhan (Рroblems of engineering and professional education, 2022)
The introduction of modem methods in the work of the teacher is an important condition for improving the learning process, creating a favorable developing environment for the development of professionally significant skills of the future specialist. A significant drawback in the field of application of teaching methods is the underestimation of the benefits of using computer technology in teaching engineering graphics, the uniformity of the methods and tools used. Analyzing this deficiency, every year the possibilities are expanding to improve the quality of teaching graphic disciplines and improving the process of teaching students.